RELATIONSHIP BETWEEN SEDIMENT TEXTURE AND ABUNDANCE OF Telescopium telescopium IN THE MANGROVE ECOSYSTEM OF THE NYALO RIVER, PESISIR SELATAN, WEST SUMATRA - Armani, Shanya Puthi; Tanjung, Afrizal; Elizal, Elizal (Asian Journal of Aquatic Sciences, 2022)
The research was conducted in October-November 2021 in the Nyalo River Mangrove Ecosystem, South Coast of West Sumatra, aiming to determine the characteristics of sediment texture, an abundance of Telescopium snails (Telescopium telescopium), and the relationship between sediment particle size. The abundance of mangrove snail populations. Habitat parameters measured include physical and chemical parameters of marine waters. Station determination using purposive sampling method. Sampling locations are divided into 3 collection points or stations that are considered to represent the study area with one transect at each station. Mangrove snails were sampled using a 3m x 3m plot with three subplots placed along the transect. The results showed that the type of substrate varied at each station. The average size ranges from 3.58 – 2.05 with very fine sand classification dominating. The abundance of the mangrove snail population ranged from 1.78–14.89 ind/m2. The correlation between sediment particle size and the abundance of mangrove snail populations is related but not closely related.